Product directivity models for parametric loudspeakers - Gan, Woon-Seng (2013)
In a recent work, the beamsteering characteristics of parametric loudspeakers were validated in an experiment. It was shown that based on the product directivity model, the locations and amplitudes of the mainlobe and grating lobes could be predicted within acceptable errors. However, the measured amplitudes of sidelobes have not been able to match the theoretical results accurately. In this paper, the original theories behind the product directivity model are revisited, and three modified product directivity models are proposed: (i) the advanced product directivity model, (ii) the exponential product directivity model, and (iii) the combined product directivity model. The proposed product directivity models take the radii of equivalent Gaussian sources into account and obtain better predictions of sidelobes for the difference frequency waves. From the comparison between measurement results and numerical solutions, all the proposed models outperform the original product directivity model in terms of selected sidelobe predictions by about 10 dB.